Effect of Nano-Modified Recycled Wood Fibers on the Micro/Macro Properties of Rapid-Hardening Sulfoaluminate Cement-Based Composites - Chunyu Ma; Liang Wang; Yujiao Li; Qiuyi Li; Gongbing Yue; Yuanxin Guo; Meinan Wang; Xiaolong Zhou (Nanomaterials, 2025)
Recycled wood fiber (RWF) obtained through the multi-stage processing of waste wood serves as an eco-friendly green construction material, exhibiting lightweight, porous, and high toughness characteristics that demonstrate significant potential as a cementitious reinforcement, offering strategic advantages for environmental protection and resource recycling. In this study, high-performance sulfoaluminate cement (SAC)-RWF composites prepared by modifying RWFs with nano-silica (NS) and a silane coupling agent (KH560) were developed and their effects on mechanical properties, shrinkage behavior, hydration characteristics, and microstructure of SAC-RWF composites were systematically investigated. Optimal performance was achieved at water–cement ratio of 0.5 with 20% RWF content, where the KH560-modified samples showed superior improvement, with 8.5% and 14.3% increases in 28 d flexural and compressive strength, respectively, compared to the control groups, outperforming the NS-modified samples (3.6% and 8.6% enhancements). Both modifiers improved durability, reducing water absorption by 6.72% (NS) and 7.1% (KH560) while decreasing drying shrinkage by 4.3% and 27.2%, respectively. The modified SAC composites maintained favorable thermal properties, with NS reducing thermal conductivity by 6.8% through density optimization, whereas the KH560-treated specimens retained low conductivity despite slight density increases. Micro-structural tests revealed accelerated hydration without new hydration product formation, with both modifiers enhancing cementitious matrix hydration product generation by distinct mechanisms—with NS acting through physical pore-filling, while KH560 established Si-O-C chemical bonds at paste interfaces. Although both modifications improved mechanical properties and durability, the KH560-modified SAC composite group demonstrated superior overall performance than the NS-modified group, providing a technical pathway for developing sustainable, high-performance recycled wood fiber cement-based materials with balanced functional properties for low-carbon construction applications.